Feminization of the Isopod Cylisticus convexus after Transinfection of the wVulC Wolbachia Strain of Armadillidium vulgare. - Myriam Badawi; Pierre Grève; Richard Cordaux (PLoS ONE, 2015)
Reproductive parasites such as Wolbachia are able to manipulate the reproduction of their hosts by inducing parthenogenesis, male-killing, cytoplasmic incompatibility or feminization of genetic males. Despite extensive studies, no underlying molecular mechanism has been described to date. The goal of this study was to establish a system with a single Wolbachia strain that feminizes two different isopod species to enable comparative analyses aimed at elucidating the genetic basis of feminization. It was previously suggested that Wolbachia wVulC, which naturally induces feminization in Armadillidium vulgare, induces the development of female secondary sexual characters in transinfected Cylisticus convexus adult males. However, this does not demonstrate that wVulC induces feminization in C. convexus since feminization is the conversion of genetic males into functional females that occurs during development. Nevertheless, it suggests that C. convexus may represent a feminization model suitable for further development. Knowledge about C. convexus sexual differentiation is also essential for comparative analyses, as feminization is thought to take place just before or during sexual differentiation. Consequently, we first described gonad morphological differentiation of C. convexus and compared it with that of A. vulgare. Then, wVulC was injected into male and female C. convexus adult individuals. The feminizing effect was demonstrated by the combined appearance of female secondary sexual characters in transinfected adult males, as well as the presence of intersexes and female biases in progenies in which wVulC was vertically transmitted from transinfected mothers. The establishment of a new model of feminization of a Wolbachia strain in a heterologous host constitutes a useful tool towards the understanding of the molecular mechanism of feminization.